2018
DOI: 10.1177/1747021818783722
|View full text |Cite
|
Sign up to set email alerts
|

The lower bounds of massive memory: Investigating memory for object details after incidental encoding

Abstract: Visual long-term memory capacity appears massive and detailed when probed explicitly. In the real world, however, memories are usually built from chance encounters. Therefore, we investigated the capacity and detail of incidental memory in a novel encoding task, instructing participants to detect visually distorted objects among intact objects. In a subsequent surprise recognition memory test, lures of a novel category, another exemplar, the same object in a different state, or exactly the same object were pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
(52 reference statements)
2
7
0
Order By: Relevance
“…Thus, the representation of the studied item might be noisy, and the performance in the memory studies might result from gist-based representations rather than storing detailed information about the stimuli. A similar finding of a rather low-level detailed representation was observed in the incidental encoding paradigm ( Draschkow et al, 2019 ), in which participants’ memory was tested using the Yes/No task. Again, the accuracy was lower than that in the original study by Brady et al (2008) .…”
Section: Introductionsupporting
confidence: 73%
“…Thus, the representation of the studied item might be noisy, and the performance in the memory studies might result from gist-based representations rather than storing detailed information about the stimuli. A similar finding of a rather low-level detailed representation was observed in the incidental encoding paradigm ( Draschkow et al, 2019 ), in which participants’ memory was tested using the Yes/No task. Again, the accuracy was lower than that in the original study by Brady et al (2008) .…”
Section: Introductionsupporting
confidence: 73%
“…Old-new recognition (ONR) probes, by contrast, may force observers to query memory for additional details of the encoded event, possibly reducing the likelihood of familiarity-based recognition judgments (Cunningham et al, 2015). For instance, Draschkow, Reinecke, Cunningham, and Võ (2018) recently used ONR probes to show that sensitivity decreased for "state" lures (e.g., an old object presented in a different physical state) relative to exemplar lures (e.g., a different category-exemplar relative to the old object) for incidentally encoded objects, although such a difference was not observed in previous work using 2-AFC probes (e.g., Brady et al, 2008;Cunningham et al, 2015). While it is possible that observers are more likely to query memory for a specific memory trace when probed by ONR relative to AFC probes, prior research suggests that AFC tests populated with within-category lures encourage participants to retrieve detailed memories (e.g., Guerin, Robbins, Gilmore, & Schacter, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…More often, we engage in goal-directed behavior, such as setting the table or looking for the salt, during which location and identity representations of the surrounding objects are generated "on the fly". There is strong support for reliable memory of incidentally encoded items (Castelhano & Henderson, 2005;Draschkow et al, 2014;Draschkow, Reinecke, Cunningham, & Võ, 2018;Draschkow & Võ, 2017;Hollingworth, 2012;Hout & Goldinger, 2010, 2012Kit et al, 2014;Võ & Wolfe, 2012, 2013bWilliams, 2010;Williams, Henderson, & Zacks, 2005;Wolfe, Alvarez, Rosenholtz, Kuzmova, & Sherman, 2011), but the importance of probing LTM content which was formed incidentally really becomes apparent when it is used to guide proactive behavior in naturalistic environments. Võ and Wolfe (2012) demonstrated that attention is most profoundly influenced by item memory established during search ("looking for"), compared to explicit memorization and free viewing in complex scenes ("looking at").…”
Section: Introductionmentioning
confidence: 99%